1994
DOI: 10.1111/j.1476-5381.1994.tb13204.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on the affinities of ATP derivatives for P2X‐purinoceptors in rat urinary bladder

Abstract: 1 Radioligand binding assays have been used to determine the affinities of a series of ATP derivatives with modifications of the polyphosphate chain, adenine and ribose moieties of the ATP molecule for[3H]-z,P-methylene ATP ([3H]-a,P-MeATP) binding sites in rat urinary bladder.2 The replacement of the bridging oxygen in the triphosphate chain of ATP (pIC50 = 5.58) with a methylene or imido group markedly increased the affinity (691 fold in IC50 values for P,V-imidoATP, 15fold for P,y-methylene ATP), and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…We indeed present evidence that the labeling reaction saturates with increasing NCS-ATP concentrations and is pharmacologically prevented by ATP or by the competitive antagonist TNP-ATP. In addition, we found that the affinity labeling is dependent on the presence of the ATP phosphate tail, because contrary to NCS-ATP no substantial labeling arises at low concentrations of NCS-Ado, a poor P2X ligand (27). Finally, we showed that modification of the side chain at N140 and L186 positions either genetically by site-directed mutagenesis or chemically by MTS derivatives of substituted cysteine profoundly alters ATP function.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…We indeed present evidence that the labeling reaction saturates with increasing NCS-ATP concentrations and is pharmacologically prevented by ATP or by the competitive antagonist TNP-ATP. In addition, we found that the affinity labeling is dependent on the presence of the ATP phosphate tail, because contrary to NCS-ATP no substantial labeling arises at low concentrations of NCS-Ado, a poor P2X ligand (27). Finally, we showed that modification of the side chain at N140 and L186 positions either genetically by site-directed mutagenesis or chemically by MTS derivatives of substituted cysteine profoundly alters ATP function.…”
Section: Discussionmentioning
confidence: 72%
“…Second, it is known that adenosine (Ado) is a poor P2X ligand (27), and consequently its site occupancy should be lower than that of ATP. Therefore, the apparent rates of the tethering reaction by NCS-Ado should be slower than those determined by NCS-ATP.…”
Section: Resultsmentioning
confidence: 99%
“…PPADS has been shown to block P2y-mediated responses in turkey erythrocytes (Boyer et al, 1994), but is ineffective at P2y receptors in rabbit mesenteric arteries and aorta (Ziganshin et al, 1994). Reactive blue 2 has been proposed as a P2Y-purinoceptor antagonist; however, it has low selectivity, acting also at P2X-purinoceptors (Choo et al, 1980;Bo et al, 1994;Bultmann & Starke, 1994) and is effective only within a narrow concentration-range (Burnstock & Warland, 1987;Hopwood & Burnstock, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…SK&F 96365 was tested at a concentration of 15 µM, which is in the range of the IC &! values reported for different preparations [7,14,15]. Suramin is generally employed at concentrations equal to or higher than the agonist concentration [2,16,17].…”
Section: Ca 2 + Transport Assaysmentioning
confidence: 99%